T+8=-76

Simple and best practice solution for T+8=-76 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for T+8=-76 equation:


Simplifying
T + 8 = -76

Reorder the terms:
8 + T = -76

Solving
8 + T = -76

Solving for variable 'T'.

Move all terms containing T to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + T = -76 + -8

Combine like terms: 8 + -8 = 0
0 + T = -76 + -8
T = -76 + -8

Combine like terms: -76 + -8 = -84
T = -84

Simplifying
T = -84

See similar equations:

| 14y-6=11y-27 | | 5x+7+9x-63= | | 3.2k=49 | | 3/4x5= | | 24uw^2y^4-28u^6w^9=0 | | G+73=15 | | (6r+2+8r^3)-(5r^3-11-8r^5)-(6r+9r^5)=0 | | 38+-3=50+-5x | | I=122m | | 45/10=x/54 | | 4t+6t-7= | | 2q=-16 | | 5x+7+9x-63=60 | | 4x-5x^2=-x^3 | | -3t=-6 | | 3x+21-2y=3 | | 0.1x-0.5z-15=1 | | 10x+10-6x=22 | | 6.8r-2=5.8r-2 | | sin64=p/34 | | 2(1-7m)=-9n+47 | | 5(3x+5)-8x-6=164 | | 20+x=56 | | 12x+18=9+12 | | 2.4x-2.6=17 | | 6(1-7x)=-33-3x | | 5(2c+7)+-3c=7(c+5) | | W=wy | | Y=1/8-3x-2 | | -8(1+8r)=-520 | | v=4/3(3.14)3^3 | | -9+4n+18=7n-24 |

Equations solver categories